1995
DOI: 10.1128/iai.63.8.3218-3221.1995
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recombinant tetanus toxin derivatives suitable for vaccine development

Abstract: Recombinant derivatives of tetanus toxin (TeTx) were isolated and used to immunize mice. Recombinant TeTx light chain, a derivative of fragment C that had lost the ability to bind neurons, and a recombinant TeTx holotoxoid that could protect mice against TeTx challenge were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Each of these domains consists largely of b sheets joined by loops which protrude from the molecule. Our previous study analysed neuronal cell binding of a number of malE-H C fusion proteins (Figueiredo et al, 1995). Proteins M1453 containing the entire H C domain of TeNT (K865±D1315) and M338 (N944±D1315) bound avidly to primary dorsal root ganglion cells, whereas M1321 (K865±H1271) displayed no binding in this assay.…”
Section: Roles Of N-and C-termini Of H C In Ganglioside Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these domains consists largely of b sheets joined by loops which protrude from the molecule. Our previous study analysed neuronal cell binding of a number of malE-H C fusion proteins (Figueiredo et al, 1995). Proteins M1453 containing the entire H C domain of TeNT (K865±D1315) and M338 (N944±D1315) bound avidly to primary dorsal root ganglion cells, whereas M1321 (K865±H1271) displayed no binding in this assay.…”
Section: Roles Of N-and C-termini Of H C In Ganglioside Bindingmentioning
confidence: 99%
“…Studies of the ganglioside binding properties of the H C fragment employing deletion mutants expressed in Escherichia coli (Halpern and Loftus, 1993;Figueiredo et al, 1995) have shown that some mutants lacking the Nterminal region of H C could still bind gangliosides and neuronal cells, but those lacking carboxy-terminal amino acids were defective in binding. The studies by Halpern and Loftus (1993) suggested an essential role for the carboxy-terminal 10 amino acids (residues 1306±1315) of H C in both ganglioside and neuronal cell binding.…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate proof-of-principle for cell-free bioconjugate vaccine production, we first set out to express a set of carrier proteins that are currently used in FDA-approved conjugate vaccines. Producing these carrier proteins in soluble conformations in vitro represented an important benchmark because their expression in living E. coli has proven challenging, often requiring purification and refolding of insoluble product from inclusion bodies (Haghi et al, 2011;Stefan et al, 2011), fusion of expression partners such as maltose-binding protein (MBP) to increase soluble expression (Figueiredo et al, 1995;Stefan et al, 2011), or expression of truncated protein variants in favor of the full-length proteins (Figueiredo et al, 1995). In contrast, cell-free protein synthesis approaches have recently shown…”
Section: Resultsmentioning
confidence: 99%
“…While MBP is not a licensed carrier, it has demonstrated immunostimulatory properties (Fernandez et al, 2007) and when linked to O-PS was found to elicit polysaccharide-specific humoral and cellular immune responses in mice (Ma et al, 2014). Similarly, the TT domains, TTlight and TTc, have not been used in licensed vaccines, but are immunostimulatory and individually sufficient for protection against C. tetani challenge in mice (Figueiredo et al, 1995). To enable glycosylation, all carriers were modified at their C-termini with 4 tandem repeats of an optimal bacterial glycosylation motif, DQNAT (Chen et al, 2007).…”
Section: Figurementioning
confidence: 99%
“…The function of the lectin like jelly role H CN -domain of H C that connects H N and H CC is still unresolved. Whereas the H CN -domain of TeNT does not bind to rat primary dorsal root ganglionic cells (Figueiredo et al 1995) and nerve growth factor-differentiated PC12 cells (Herreros et al 2000a), a low affinity binding of H CN of BoNT/A to phosphatidylinositolmonophosphate incorporated in sphingomyelin enriched microdomains of the immortalized motor neuron cell line NSC-34 was reported recently (Muraro et al 2009). Nevertheless, a direct involvement of H CN A in the translocation step could be ruled out lately (Fischer et al 2008).…”
mentioning
confidence: 99%